P2X Receptors Inhibit NaCl Absorption in mTAL Independently of Nitric Oxide - Svendsen, Samuel L.; Isidor, Søren; Praetorius, Helle A.; Leipziger, Jens (Frontiers in Physiology, 2017)
Activation of basolateral P2X receptors markedly reduces NaCl absorption in mouse medullary thick ascending limb (mTAL). Here we tested the role of nitric oxide (NO) in the ATP-mediated (P2X) transport inhibition. We used isolated, perfused mTALs from mice to electrically measure NaCl absorption. By microelectrodes we determined the transepithelial voltage (Vte) and transepithelial resistance (Rte). Via these two parameters, we calculated the equivalent short circuit current, I´sc as a measure of the transepithelial Na+ absorption. Basolateral ATP (100 µM) acutely induced reversible inhibition of Na+ absorption (24 ± 4%, n=10). Addition of L-arginine (100 µM) had no apparent effect on the ATP-induced transport inhibition. Acute reduction of extracellular [Ca2+] to either 100 nM or 0 nM by addition of EGTA had no effect on the ATP-induced transport inhibition. In the presence of the NO synthase (NOS) inhibitor L-NAME (100 µM) and/or ODQ to inhibit the guanylyl cyclase, the ATP effect remained unaffected. Increasing the concentration and incubation time for L-NAME (1 mM) still did not reveal any effect on the ATP-mediated transport inhibition. Acute addition of the NO donors SNAP (100 µM) and Spermine NONOate (10 µM) did not alter tubular transport. High concentrations of L-NAME (1 mM) in itself, however, reduced the transepithelial transport significantly. Thus, we find no evidence for nitric oxide (NO) as second messenger for P2X receptor-dependent transport inhibition in mTAL. Moreover, Ca2+ signalling appears not involved in the ATP-mediated effect. It remains undefined how P2X receptors trigger the marked reduction of transport in the TAL.